Environmental Economics - C. Field Barry (Mc Graw-Hill, 2005)
Twenty-one chapters covering Cost and Benefits of Environmental Policy, Environmental Analysis, Policy Analysis, US Policy (Air Pollution, Toxic Wastes, State and Local Issues), and International Environmental Issues.